Efisiensi Layanan Publik Melalui BPR: Digitalisasi Proses Mutasi Pegawai di Disdikbud Tabalong - Muhammad Rafly Hidayat; Wildan Suharso (Jurnal Algoritma, 2026)
The employee transfer process at the Tabalong Regency Education and Culture Office (Disdikbud) is still manual, resulting in completion times of up to one month, susceptibility to errors, and reduced applicant satisfaction. This study applies digitalization-based Business Process Reengineering (BPR) to redesign the process flow. The research method uses Business Process Model and Notation (BPMN) 2.0 for process modeling and ASME standards for throughput efficiency testing. The results show that the existing process throughput efficiency is only 1.05% with a total time of 69,005 minutes. The proposed web-based system with real-time document verification automation, electronic signatures, and automatic notifications increases efficiency to 100% in just 110 seconds (1.8 minutes). This implementation is in line with the National SPBE agenda and can be replicated in other agencies.